The swallow element and muscular activations - Campos, M.; Sousa, F.; Lebre, E. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
Swallow is a strength hold element performed on rings routines by the world best gymnasts. The competitive value and the elements intrinsic difficulty are the main reasons to study it from the biomechanical point of view. The aim of this study was to characterize the swallow element in order to identify the muscular activation of the different muscles to create strategies of progression to learn this skill. Surface electromyography was used to evaluate 8 muscles during swallow performance in competitive contest. Results suggest that to perform the swallow element is necessary to stabilize the shoulder joint by activating infraspinatus, serratus anterior and trapezius inferior muscles, which will allow the anterior muscles to support the body mass in balance.